Inter-mineral Mg isotope fractionation during hydrothermal ultramafic rock alteration: Implications for the global Mg-cycle - Beinlich, Andreas; Mavromatis, V.; Austrheim, H.; Oelkers, E. (2014)
Both riverine and ocean waters are enriched in 24Mg compared to the homogeneous chondritic Mg isotopic composition of the Earth's mantle requiring a fractionation step that is generally attributed to low temperature continental crust weathering. Here we present new observations that indicate that this 24Mg enrichment of surface waters may originate from Mg isotope fractionation during the hydrothermal alteration of primary silicate minerals. Mineral separates of hydrothermally altered ultramafic rocks were collected from three different localities in Norway. Coexisting olivine and serpentine exhibit invariant Mg isotope ratios suggesting that serpentinization does not fractionate Mg isotopes. In contrast, carbonation results in significant inter-mineral Mg isotope fractionation between the antigorite, magnesite, and talc. The carbonation of the natural samples is constrained by O isotope thermometry at ~275°C and hence closes the temperature gap between previous investigations of the natural distribution of Mg isotopes during surface weathering and magmatic processes. The precursor antigorite has an isotopic composition of d26Mg (DSM-3) = - 0.11 ± 0.05‰, whereas the talc is enriched in 26Mg with mean dMg26=0.17±0.08‰ and the magnesite is depleted in 26Mg with mean dMg26=-0.95±0.15‰. As carbonate minerals dissolve faster than silicate minerals, the chemical weathering of carbonated ultramafic and by analogy mafic rocks on the continents will yield isotopically lighter Mg to natural surface waters consistent with field observations. Moreover, the Mg fractionation observed in this study suggests that sub-seafloor hydrothermal carbonation may be a significant contribution to the Mg isotopic composition of ocean water. © 2014 Elsevier B.V.